Active site mapping of Loxosceles phospholipases D: Biochemical and biological features - Vuitika, L.; Chaves-Moreira, D.; Caruso, I. [UNESP]; Lima, M. A.; Matsubara, F. H.; Murakami, M. T.; Takahashi, H. K.; Toledo, M. S.; Coronado, M. A. [UNESP]; Nader, H. B.; Senff-Ribeiro, A.; Chaim, O. M.; et al. (Elsevier, 2016)
Brown spider phospholipases D from Loxosceles venoms are among the most widely studied toxins since they induce dermonecrosis, triggering inflammatory responses, increase vascular permeability, cause hemolysis, and renal failure. The catalytic (H12 and H47) and metal-ion binding (E32 and D34) residues in Loxosceles intermedia phospholipase D (LiRecDT1) were mutated to understand their roles in the observed activities. All mutants were identified using whole venom serum antibodies and a specific antibody to wild-type LiRecDT1, they were also analyzed by circular dichroism (CD) and differential scanning calorimetry (DSC). The phospholipase D activities of H12A, H47A, H12A-H47A, E32, D34 and E32A-D34A, such as vascular permeability, dermonecrosis, and hemolytic effects were inhibited. The mutant Y228A was equally detrimental to biochemical and biological effects of phospholipase D, suggesting an essential role of this residue in substrate recognition and binding. On the other hand, the mutant C53A-C201A reduced the enzyme's ability to hydrolyze phospholipids and promote dermonecrosis, hemolytic, and vascular effects. These results provide the basis understanding the importance of specific residues in the observed activities and contribute to the design of synthetic and specific inhibitors for Brown spider venom phospholipases D.
Keywords: Activity modulation; Brown spider venom; Phospholipase D; Site-directed mutagenesis